(untitled) (Indonesian Tourism Justice Review, 2024)
Tourism is a major source of income in Indonesia, but the economic benefits are often unevenly distributed, with local communities—especially those in rural and remote areas—frequently excluded from the profits. This paper explores the concept of economic justice in the context of Indonesia’s tourism industry, investigating how tourism development can be more inclusive and equitable for local populations. The study examines how tourism revenues are allocated between large corporations, local businesses, and the communities that host tourists. It highlights case studies from popular tourist destinations like Bali and Lombok, where the local economy has seen both positive and negative impacts from tourism. The research focuses on issues such as employment opportunities for local people, access to resources, and the role of small businesses in the tourism supply chain. The paper discusses the importance of community-based tourism models, which emphasize local ownership, cultural preservation, and the fair distribution of economic benefits. It also evaluates government policies that promote inclusive tourism development and suggests strategies for ensuring that local communities benefit from the tourism boom while mitigating the potential for exploitation and inequality.